2020
DOI: 10.1503/cjs.007119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of trauma resources in rural northern Alberta identifies opportunities for improvement

Abstract: Background: The care of rural trauma patients in northern Alberta can be extremely challenging because of the vast geographic area, the limited access to health care facilities and the lack of adequate resources to manage severe injuries. Identifying gaps in equipment and personnel in rural centres can provide opportunities for improving the care of injured patients in these environments. We conducted a survey based on Canadian Accreditation Council quality indicators to evaluate trauma infrastructure and huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…First Nations patients tend to live in more rural areas than non-First Nations patients in Alberta, 7 and ambulances may more frequently bypass small community hospitals when transporting acute cases. 64 Future research to distinguish triage outcomes across more ethnic groups in Canada would also be valuable. Finally, our results incidentally showed greater odds of higher acuity triage scores in Calgary than other zones; we cannot explain this finding, so this could be an object of future research.…”
Section: Researchmentioning
confidence: 99%
“…First Nations patients tend to live in more rural areas than non-First Nations patients in Alberta, 7 and ambulances may more frequently bypass small community hospitals when transporting acute cases. 64 Future research to distinguish triage outcomes across more ethnic groups in Canada would also be valuable. Finally, our results incidentally showed greater odds of higher acuity triage scores in Calgary than other zones; we cannot explain this finding, so this could be an object of future research.…”
Section: Researchmentioning
confidence: 99%
“…This higher strain on healthcare resources could negatively impact the care of patients with fireworks-related injuries, especially in the state’s many rural regions. Others have shown that rural critical access hospitals (CAHs) may not all be equipped and staffed to provide adequate care for trauma patients 19 20. Jiang et al assessed trauma resources in rural northern Alberta, a regional trauma system and identified deficiencies in trauma-specific personnel training and equipment availability 19.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that rural critical access hospitals (CAHs) may not all be equipped and staffed to provide adequate care for trauma patients 19 20. Jiang et al assessed trauma resources in rural northern Alberta, a regional trauma system and identified deficiencies in trauma-specific personnel training and equipment availability 19. Pilkey et al assessed paediatric readiness of CAHs and noted several challenges affecting low-volume to medium-volume CAHs when it comes to paediatric readiness, including the lack of policies for paediatric emergency care and the cost of training personnel 20…”
Section: Discussionmentioning
confidence: 99%
“…The complexities of providing highquality trauma care in rural and austere environments will require novel solutions; innovative ideas; and ongoing discussion, collaboration, and research at local, national, and international levels. Other states and countries with rural populations face similar challenges and may have unique perspectives and novel solutions, [37][38][39] so we should take advantage of opportunities to share information. We hope to use the current challenges as a catalyst to implement change and improve the delivery of trauma care to patients in rural America.…”
Section: Solutions and Next Stepsmentioning
confidence: 99%